The mycoflora of wild Pink-footed Geese sampled in Iceland and Scotland, 1953 - Sladen, W J L; Austwick, P K C (Wildfowl, 1954)
An attempt was made, (i) to study the fungi isolated from the upper respiratory tracts of wild Pink-footed Geese at their breeding-grounds in Iceland and at their winter quarters in Scotland, in order to discover whether they harboured Aspergillus fumigatus in the wild, and (ii) to test suitable methods for collecting samples in the field under adverse conditions. Cultures were made by streaking throat-swabs on to Sabouraud's dextrose agar slopes and neither these nor the controls revealed A. fumigatus or any other potential pathogenic fungus, but the isolates obtained showed that the quality and quantity of the fungus content of the upper respiratory tracts of the geese may be dependent on their environment. Suggestions are made for improving technique. A species of Ascomycete grown from the throats of three geese in Iceland appears to be new to science.